Comprehensive Analysis of a Long Noncoding RNA-Associated Competing Endogenous RNA Network in Wilms Tumor. (25th June 2020) - Zhang, Feng; Zeng, Liping; Cai, Qinming; Xu, Zihao; Liu, Ruida; Zhong, Haicheng; Mukiibi, Robert; Deng, Libin; Tang, Xiaoli; Xin, Hongbo
Long noncoding RNA (lncRNA) plays crucial roles in various biological processes of different cancers, especially acting as a competing endogenous RNA (ceRNA). However, the role of lncRNA-mediated ceRNA in Wilms tumor (WT), which is the most common malignant kidney cancer in children, remains unknown. In present study, RNA sequence profiles and clinical data of 125 patients with WT consisting of 119 tumor and 6 normal tissues from Therapeutically Applicable Research To Generate Effective Treatments database were analyzed. A total of 1833 lncRNAs, 156 microRNAs (miRNAs), and 3443 messenger RNAs (mRNAs) were identified as differentially expressed (DE) using "DESeq2" package. The lncRNA-miRNA-mRNA ceRNA regulatory network involving 748 DElncRNAs, 33 DEmiRNAs, and 189 DEmRNAs was constructed based on miRcode, Targetscan, miRTarBase, and miRDB database. Gene Ontology term and Kyoto Encyclopedia of Genes and Genomes pathway analyses revealed that DEmRNAs were mainly enriched in cell proliferation-related processes and tumor-related pathways, respectively, and 13 hub genes were identified by a protein–protein interaction network. Survival analysis detected 48 lncRNAs, 7 miRNAs, and 16 mRNAs to have significant impact on the overall survival of patients with WT. Additionally, we found that 6 DElncRNAs with potential prognostic value were correlated with tumor stage ( DENND5B-AS1 ) and histologic classification ( TMPO-AS1, RP3-523K23.2, RP11-598F7.3, LAMP5-AS1, and AC013275.2 ) of patients with WT. Our research provides a great insight into understanding the molecular mechanism underlying occurrence and progression of WT, as well as the potential to develop targeted therapies and prognostic biomarkers.